Preoperative surgical planning for an internal carotid artery invading brain tumor - Hendrikus Bolly; Bilzardy Ferry Zulkifli; Achmad Adam (Neurologico Spinale Medico Chirurgico, 2020)
Brain tumor such as a meningioma can invade the adjacent internal carotid artery (ICA). Surgical approach to resect the tumor has to consider the level of ICA and how the depth of tumor cells invade into the artery layer. Knowledge of the basic mechanism about how the tumor cells invade the lumen and layer of the vessels is essential in perioperative preparation. Here we reported our unpredictable case findings of transient intraluminal obstruction of the arterial wall by tumor tissue in angiography examination as well as preoperative planning to resect the tumor and predictors of the patient’s outcome.